Non-ammonolysis synthesis and characterisation of environmentally benign yellow pigments based on calcium–tantalum perovskite oxynitrides. Issue 12 (19th May 2022) - Sakata, Takuya; Urushidani, Sohta; Tarutani, Naoki; Katagiri, Kiyofumi; Inumaru, Kei; Koyama, Kyohei; Iwata, Nozomu; Masubuchi, Yuji
Abstract : Calcium–tantalum based perovskite oxynitrides were successfully prepared without ammonolysis. The colour of La 3+ -doped CaTa(O, N)3 was comparable to that of CaTaO2 N prepared by ammonolysis and inorganic yellow pigments using heavy metals. Abstract : Calcium–tantalum-based perovskite oxynitrides were synthesised as candidates for environmentally benign inorganic yellow pigments. The compounds were prepared via a urea-nitriding method, which does not involve a harmful ammonolysis process. Rapid single-phase synthesis was achieved under the optimum conditions, and only removable by-products were generated. Although the colours and bandgap energies of the obtained calcium–tantalum oxynitrides, CaTa(O, N)3, fell short of those of CaTaO2 N synthesised by ammonolysis, they were made comparable by doping with La 3+ . Among the samples synthesised in this study, the most brilliant yellow hue was achieved with Ca0.8 La0.2 Ta(O, N)3, which has lightness ( L *) and yellowness ( b *) values comparable to those of conventional inorganic yellow pigments. In this synthetic method, harmful substances are eliminated both from the products and the synthesis process. In addition, the short heat-treatment duration enables the products to be obtained as fine powders suitable for pigment applications. Calcium–tantalum-based perovskite oxynitrides prepared by the strategy developed in this study have potential applications as environmentally benign yellow pigments.